Biphasic Modulation of Neutrophil Migration by Aqueous Extracts of Uncaria tomentosa in Murine Lung - Roque, Noelia (2009)
In the history of medicine, the treatment of disease has been influenced by an intimate contact with nature. A mice model of lipopolysaccharide (LPS)-induced acute lung injury was used to evaluate the protective effects of long-term water-soluble administration ad libitum of Uncaria tomentosa extracts (20 gr/L; UTE) in lung inflammation. Swiss mice had LPS (1,67µg/ml) instilled intranasally 3hs before sacrificed, and were then pre-treated with UTE for 7, 15, 30 or 90 days or with a single dose of dexamethasone (2,5 mg/kg, DX). Inflammatory cell concentration was measured in the bronchoalveolar fluid (BALF) and histology was performed. No acute or chronic toxicity signs were observed in the clinical status. In addition, body weight, food consumption, organ weight, kidney, liver, and lung pathology were not found to be affected by the UTE treatments. UTE or DX significantly reduced the lung edema, exudation and lung injury histology for 7 and 90 day treatments. In addition, pre-treatment with UTE revealed a biphasic attenuated recruitment in BALF from neutrophils at 7 and 90 days induced by endotoxin exposure compared to the control (p<0.05). These data suggest that UTE initially induces a nonspecific response that is transient protection from PMNs migration into the lung mice.